In-Silico Analysis of Coumarins for Neurodegenerative, Infectious and Metabolic Diseases - Divya, D; Kalpana, A (Київський національний університет імені Тараса Шевченка, 2025)
The present study evaluated the binding affinities for a set of coumarins against five key targets which are relevant for anti-Alzheimer's, antimicrobial, anticancer, anti-tuberculosis, and anti-adipogenic activities. Docking score analysis revealed that 3''-Demethylchartreusin 71, Chartreusin 69 and Fabiatrin 70 and coumarin pyrazole hybrid 298 exhibited significant binding interactions with the targets, making them as the promising lead compounds. Key stabilizing interactions, including H-bonding, π-π, π-σ, π-anion/cation, and π-alkyl interactions, have been analyzed. In-silico drug-likeness analysis was performed on all the coumarins, and another nine coumarins were identified as promising molecules with acceptable pharmacokinetic properties, making them potential multitargeted drug candidates.
Keywords: Coumarin hybrids; Anti-Alzheimer; Antimicrobial; Anticancer; Anti-adipogenic activities